A política pública de segurança em Mossoró-RN: uma avaliação de processo da implantação da guarda civil (2009-2013) - Pimenta, Melissa Rafaela Costa (2014)
The subject of public safety is part of the academic and popular discussions, due to several factors that act in society culminating in an increasing criminality. The importance of the evaluation of public policies in this context consists in a possible control tool, monitoring and necessary adjustments to the government to make the necessary changes. Given this reality, it is thought the research problem: how Mossoró (RN) city has implemented his public security policy? In general guideline of the research, we work with the following hypothesis: the own formulation of the National Policy of Public Safety there are elements that hinder the implementation of a public policy of municipal security in Mossoró. The objective of this research is to evaluate the existing security public policy in the city of Mossoró, by the elements that facilitate and/or hamper its implementation, through the actions of municipal government in the activities of the Mossoro Civil Guard (GCM). For this, a review of the implementation process was conducted, specifically its subprocesses of selection, training, and logistical or operational. Was used bibliographical research, documental primary and secondary, and field research, with conducting of interviews. It was found that with a staff of 197 guards, and with five years of creation, the actions developed by this institution refer to an early implementation of the municipal security policy. The guard has the basic pattern selection, part of function relocation and part of public tender. The formation occurs in an introductory way, however, not complete and specific, for the function performance. Its operability is limited by the number of existing effective and by the physical structure that has not matching the demand yet, which touches on the municipal budgetary reality of direct resource intended to safety. It was found the absence of a municipal plan of public security with principles, guidelines and goals that could direct the actions of the guard. It is concluded that despite of the implementation of the GCM Mossoró have not achieved, within the parameters of efficiency, efficacy and effectiveness have played their actions, projects and programs, it could trigger a process of opening for construction of a municipal security policy. As well as break with the paradigm of municipal actions just meant for surveillance of public property, interaction affirmative for the prevention of violence and crime